Analysis of Clinically Significant Double Thrombophilias Versus Single Thrombophilias During Pregnancy [8R]. (May 2016) - Carroll, Rachel C.; Booker, Whitney; Gupta, Simi; Rebarber, Andrei; Fox, Nathan; Lam-Rachlin, Jennifer
Abstract : INTRODUCTION: Pregnancy is a hypercoaguable state and for patients with inherited thrombophilias, it may represent a period of heightened risk. There have been some data suggesting that women with double thrombophilias (DT) have an even greater risk of obstetrical complications. A paucity of data analyzing the impact of DT when compared to single thrombophilias (ST) has been published due to the rarity of these conditions identified in patients. METHODS: This is a retrospective cohort study of all patients in a single maternal-fetal medicine practice who were found to have a clinically significant inherited thrombophilia and treated with anticoagulation between 2005–2013. Thrombophilias evaluated included: Factor V Leiden (FVL), Prothrombin G20210A gene mutation (PGM), Protein S deficiency (PSD), Protein C deficiency (PCD), and Antithrombin III deficiency (ATIII). DT were defined as the presence of 2 clinically significant thrombophilias or homozygosity for FVL or PGM. Patients with DT were compared to those patients with ST. Demographic and obstetrical outcome data were collected and compared between the two groups. The data was analyzed with Pearson's chi-squared or Student's t test as appropriate. RESULTS: 156 pregnancies with clinically significant thrombophilias were identified. Demographic characteristics were equivalent between the two groups. There were no significant differences for obstetrical outcomes between patients for birthweight <10%, intrauterine fetal demise, preterm delivery (spontaneous or iatrogenic), pregnancy induced hypertension, or neonatal intensive care unit admission. CONCLUSION: There were no significant differences in obstetrical outcomes for patients with clinically significant DT versus ST when treated with anticoagulation. This information may be reassuring for patients with DT.